2020
DOI: 10.1186/s12936-020-3103-5
|View full text |Cite
|
Sign up to set email alerts
|

Health gains and financial risk protection afforded by public financing of selected malaria interventions in Ethiopia: an extended cost-effectiveness analysis

Abstract: Background: Malaria is a public health burden and a major cause for morbidity and mortality in Ethiopia. Malaria also places a substantial financial burden on families and Ethiopia's national economy. Economic evaluations, with evidence on equity and financial risk protection (FRP), are therefore essential to support decision-making for policymakers to identify best buys amongst possible malaria interventions. The aim of this study is to estimate the expected health and FRP benefits of universal public financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 24 publications
(26 reference statements)
4
34
0
1
Order By: Relevance
“…Literature has shown that implementing more effective malaria surveillance and control methods can result in greater economic benefits (15)(16)(17)(18)(19)(20)(21). Presently, malaria management in Fujian Province is incorporated into overall public health efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that implementing more effective malaria surveillance and control methods can result in greater economic benefits (15)(16)(17)(18)(19)(20)(21). Presently, malaria management in Fujian Province is incorporated into overall public health efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that implementing more effective malaria surveillance and control methods can result in greater economic bene ts (15)(16)(17)(18)(19)(20)(21). Presently, malaria management in Fujian Province is incorporated into overall public health efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that implementing more effective malaria monitoring and control measures can produce economic bene ts [15][16][17][18][19][20][21]. At present, malaria monitoring measures in Fujian Province have been incorporated into overall public health efforts.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the literature on the economic evaluation of malaria [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], held discussions with the research team, consulted the experts on malaria, and then determined the typical bene t indicators. The economic bene ts included the direct medical and non-medical bene ts of avoiding hospitalization and missed work bene ts of avoiding hospitalization.…”
Section: Determining Bene T Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation